Northwest history. Mining. Discovery. 1936-01-17 (1936)
Evis gold mines reports ore find - Evis Gold Mines corporation has just struck ore 12 feet wide that assays $8 to the ton in its property 22 miles from Ketchikan, according to Homer Tillley, a mine operator of Tacoma, who is at the Davenport. Spokane men are among the stockholders.